Library effectiveness of an IBPYP (International Baccalaureate Primary Years Programme) school. - Yvonne Carolyn Krishnan. (2008)
This dissertation explores the effectiveness of the school library in an inquiry-based programme, the IBPYP (International Baccalaureate Primary Years Programme).